Reported Diabetes Mellitus Prevalence Rates in the Colombia Healthcare System from 2009 to 2012: Analysis by Regions Using Data of the Official Information Sources - Noël C. Barengo; Diana Carolina Tamayo (International Journal of Endocrinology)
The objective of this study was to describe the reported diabetes mellitus (DM) prevalence rates of the 20–79-year-old population in Colombia from 2009 to 2012 reported by the healthcare system. Information on number of patients treated for DM was obtained by the Integral Information System of Social Protection (SISPRO), the registry of the Ministry of Health and Social Protection, and the High Cost Account (CAC), an organization to trace high expenditure diseases. From both sources age-standardized reported DM prevalence rates per 100.000 inhabitants from 2009 to 2012 were calculated. Whereas the reported DM prevalence rates of SISPRO revealed an increase from 964/100.000 inhabitants (2009) to 1398/100.000 inhabitants in 2012 (mean annual increase 141/100.000; p value: 0.001), the respective rates in the CAC register were 1082/100.000 (2009) and 1593/100.000 in 2012 (mean annual increase 165/100.000; p value: 0.026). The number of provinces reporting not less than 19% of the highest national reported DM prevalence rates (1593/100.000) increased from two in 2009 to ten in 2012. Apparently, the registries and the information retrieving system have been improved during 2009 and 2012, resulting in a greater capacity to identify and report DM cases by the healthcare system.